Understanding the Potential of mRNA as Biomarker to Revolutionize Diagnosis of Colorectal Cancer - Das, Rina; Mehta, Dinesh Kumar; Gupta, Nidhi (Drug Research, 2024)
In the realm of medical research, the quest to find effective biomarkers for various diseases has always been a top priority. Colorectal cancer (CRC), one of the leading causes of cancer-related deaths worldwide, is no exception. The emergence of microRNA (mRNA) as a potential biomarker for CRC has sparked immense interest among scientists and clinicians alike. mRNA, a molecule responsible for translating genetic information into functional proteins, presents a promising avenue for early detection and personalized treatment of this deadly disease. By analyzing the specific patterns and levels of mRNA expression in CRC cells, researchers have the ability to identify signatures that can aid in accurate diagnosis, predict patient prognosis, and even guide targeted therapies. This breakthrough in molecular biology not only enhances our understanding of CRC but also holds the potential to revolutionize the field of cancer diagnostics and treatment. In this article, we will delve deeper into the potential of mRNA as a biomarker for CRC, exploring its benefits and challenges in the field of cancer research.MicroRNA as potential biomarker for early diagnosis, differentiating various stages, interpreting the success of postoperative curative surgery and predicting early relapse of Colorectal cancer.
Keywords: colorectal cancer; colorectal adenoma; microRNA; non-invasive; CRC patients